Comparison of the Effect of Preoperative Skin Prepartion with Povidone-Iodine and Chlorhexidine-Gluconate on Surgical Site Infection in Laparotomy Patients - Fardin Amiri; Arash Khajehvand; Sedigheh Hannani; Nemamali Azadi (Tehran University of Medical Sciences, 2022)
Background and Aim: Surgical site infection (SSI) is one of the most common health-care associated infections. Using proper antiseptic solutions for preoperative surgical site skin preparation (skin prep) is one of the methods to reduce SSIs. The purpose of this study was to compare the effect of preoperative surgical site skin preparation with povidone-iodine and chlorhexidine-gluconate on the rate of SSI in laparotomy patients. Materials and Methods: A total of 70 Laparotomy surgery patients who referred to Firoozgar hospital in Tehran from May to September of 2021 were included in this clinical trial. Patients were randomly allocated into two groups which were treated with povidone-iodine(PVI) or chlorhexidine-gluconate (CHG) for surgical site skin prep. Skin prep was done with standard rotational method in two steps by the researcher for each group by using of PVI and CHG. SSI incidence was assessed by a researcher-made check list and also over post-surgical follow up visits by the surgeon. We used Fischer's exact test, t-test, Chi-square and Cochrane's Q-test to analyze the collected data. Results: SSI was seen in five patients (14.29%) of PVI group and one patient (2.86%) of CHG group. Although the SSI incidence in PVI group was 5.54 times more than CHG group, still the difference wasn't statistically significant (P=0.198). Comparing the incidence of SSI's in 24 hours after surgery (0%) and 30 days after surgery (8.57%) in both groups revealed that using these antiseptics for skin prep was effective in preventing SSI (P<0.001). SSI incidence was also associated with two days of patient's hospital admission time (P=0.001). Conclusion: The result of this study revealed that the occurrence of SSI in PVI group was 5.54 times more than CHG group. However, the difference was not statistically significant. So both of these antiseptics can be used for surgical site skin prep.